(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
In managerial education there are several methods that allow to develop indispensable competitions in order to acquiere effective knowledge. Besides the traditional methodology, there are learning methods based on the experience which try to improve the quality of the education. The aim of this research is to select the technique that, from the students point of view, best develop their directive skills. For that purpose, a group of spanish students belonging to the Universidad Nacional de Educación a Distancia (UNED) have been interviewed. The results show that business games, the case method and practices in companies are the best pedagogical tools.